THE EFFECT OF RETURN ON ASSETS, DEBT TO EQUITY RATIO AND MANAGERIAL OWNERSHIP ON PRICE TO BOOK VALUE IN MINING SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) 2016-2020 PERIOD - Hasanudin, Hasanudin; Nisa, Nelisa La (Master of Management, Faculty of Economics and Business, Diponegoro University, 2023)
This study aims to find out and analyze the effect of return on asset, debt to equity ratio and managerial ownership of price to book value in mining sector companies listed on the Indonesian Stock Exchange (IDX) for the period 2016 to 2020. The population in this study used a porposive sampling technique. The data in this study uses annual reports from 20 mining sector companies with a total of 88 samples of observations. This study uses secondary data and data collection techniques. The technique used is multiple linear regression technique and uses the Statistical Product Service Solution program or SPSS version 26.The results of this study indicate that return on assets has a positive and significantly to the price to book value, the debt to equity ratio has no effect on the results positive and not significant to the price to book value. Temporary managerial ownership has no effect on negative and significant results on price to book value.